(untitled) (Jurnal Manajemen Bisnis, 2024)
This study investigates the factors influencing customer purchase intentions in GoFood. The UTAUT model integrates four essential constructs: Performance Expectancy, Effort Expectancy, Social Influence, and Trust. The research data was collected through a Google Form questionnaire with 207 respondents. Additionally, the research may inform strategic decisions for GoFood and similar platforms, helping them enhance user experiences, build trust, and ultimately increase customer purchase intentions. Based on data analysis, Social Influence, Effort Expectancy, Performance Expectancy, and Trust have negative and not significant effect on Online Purchase Intention. Trust has positive and significant effect on Performance Expectancy and Effort Expectancy.